2018
DOI: 10.21608/ajs.2018.34161
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Behavior in Soils Contained Different Silicon and Phosphorus Concentrations Using Adsorption Models [

Abstract: Silicon (Si) is an element, not essential, but is beneficial for some plants. The Freundlich model was used to describe Si adsorption on soil samples incubated with different Si and phosphorus (P) concentrations. Soil incubated samples were: T1 soil had no Si or P (control); T2, T3 and T4 soils contained 50, 100, and 200 mg Si L -1 , respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Comparing the amount of Si adsorbed in the soils by estimating adsorbed Si from Freundlich, Langmuir, and Temkin isotherms, it was observed that each soil parent material had different capacities to adsorb Si (Table 3). The differences in the values of Freundlich, Langmuir, and Temkin model parameters may be due to relative differences in the properties of the soils (McKeague and Cline, 1963b;Morsy et al, 2018). The goodness of fit for a particular model is ascertained by looking at the R 2 values (Idris and Ahmed, 2012).The study showed that the Temkin model showed superiority over the Freundlich and Langmuir model in all the soils based on regression coefficient (R 2 ) values which ranged from 0.228 (Imo shale soils) to 0.734 (coastal plains and soils), contrary to Bakheit and Pakermanjie (1993) and Gregory et al (2005)…”
Section: Comparing the Freundlich Langmuir And Temkin Adsorption Mode...mentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing the amount of Si adsorbed in the soils by estimating adsorbed Si from Freundlich, Langmuir, and Temkin isotherms, it was observed that each soil parent material had different capacities to adsorb Si (Table 3). The differences in the values of Freundlich, Langmuir, and Temkin model parameters may be due to relative differences in the properties of the soils (McKeague and Cline, 1963b;Morsy et al, 2018). The goodness of fit for a particular model is ascertained by looking at the R 2 values (Idris and Ahmed, 2012).The study showed that the Temkin model showed superiority over the Freundlich and Langmuir model in all the soils based on regression coefficient (R 2 ) values which ranged from 0.228 (Imo shale soils) to 0.734 (coastal plains and soils), contrary to Bakheit and Pakermanjie (1993) and Gregory et al (2005)…”
Section: Comparing the Freundlich Langmuir And Temkin Adsorption Mode...mentioning
confidence: 99%
“…Thus, sorption is one of the many soil processes that influence the transport and regulation of nutrient concentration in soil solution (Dandanmozd and Hosseinpur, 2010). Adsorption and desorption are usually explained through adsorption and desorption isotherms which is the amount of adsorbate (Si) on the adsorbent (soil particles) as a function of pressure (if gas) or concentration (if liquid) at constant temperature and time (Morsy et al, 2018). The adsorption isotherm…”
Section: Introductionmentioning
confidence: 99%
“…The highest value of n = 2.806 recorded for soils B (Table 3) indicates that the sorption of P unto soils particles is more favorable when compared to the soils derived from the other parent materials however this favorable P sorption process could be ascribed to low pH value (4.53) of soils B (Table 1). Morsy et al [16] have reported the influence of pH on sorption processes in soils.…”
Section: Freundlich Adsorption Isothermmentioning
confidence: 99%
“…Yu and Li [5] previously showed that when equilibrium silicate concentration was less than about 30 mg 50 mg Si L -1 together with 7 mg P L -1 (Pi1), T 6 soil content of 50 mg Si L -1 together with 10 mg P L -1 (Pi2), T 7 soil content of 100 mg Si L -1 together with 7 mg P L -1 , T 8 soil content of 100 mg Si L -1 together with 10 mg P L -1 , T 9 soil content of 200 mg Si L -1 together with 7 mg P L -1 , T 10 soil content of 200 mg Si L -1 together with 10 mg P L -1 . Technique of adsorption described by Cartes, et al [14] and Morsy, et al [17] A series of adsorption experiments was performed using sodium metasilicats benta hydrate Na 3 SiO 4 .5H 2 O solution prepared to have concentrations representing 0, 14, 28, 42 and 56 mg L -1 in combination with phosphorus at the concentrations of 50 and 100 mg L -1 , P 1 and P 2 , using Ca(H 2 PO 4 ) 2 salt. Aliquots were finally taken out, to be analyzed for Si [16].…”
Section: Introductionmentioning
confidence: 99%